ANALISIS PENAWARAN DAN PERMINTAAN EKOWISATA BEKANTAN DI HUTAN RAWA GELAM TAPIN KALIMANTAN SELATAN - Agustine, Ratna; Alikodra, Hadi Sukadi; Iskandar, Entang (Media Konservasi, 2016)
Located in South Borneo, Gelam Swamp Forest is an important ecosystem area for the conservation of proboscis monkey (Nasalis larvatus). Due to its tourism  potential, the local government have launched this area of 90 hectare into proboscis monkey ecotourism in Tapin (SK Bupati Tapin No. 188.45/060/KUM/2014). Data of supply and demand needed to the ecotourism development. The research through questionnaires, observation and literature review have been conducted during December 2015 through  June 2016. These data were analyzed using descriptive, scoring, and supply-demand analysis, so that strategy was arranged by ecotourism development. Most of potential visitors have not  yet been informed about the proboscis monkey ecotourism in Tapin, but they were motivated to visit the ecotourism area. In addition, they were interested to see the various attractions offered by the management. Besides, they considered the existence of facility, accessibility and amenity. Therefore, this area should be developed by improvingthe aspects of supply and increasing the awareness of potential visitors’ for conservation. Keywords: demand, ecotourism, Gelam Swamp Forest, supply